Effect of fruit and mint flavored Rogue® oral nicotine product use on smoking reduction and quitting in a 6-Month prospective cohort of adults who smoke cigarettes - Elliott H. McDowell; Jason N. Kennedy; Michael Feehan; Stacey A. Bell; Sarah E. Marking; Jessica P. Zdinak; Andrew R. Joyce; Michelle Humphreys (BMC, 2024)
Abstract Background Quitting cigarette smoking can substantially reduce or eliminate the risk of developing numerous chronic diseases. Use of flavored tobacco or nicotine products is commonly cited by adults who smoke cigarettes to be important in helping them reduce or quit smoking. The purpose of this analysis was to understand the association between the levels of use of flavored oral nicotine products and smoking reduction and quitting and how reduction or quitting may differ between predominant users of fruit/other versus mint flavored oral nicotine products after six months of use. Methods Participants were provided with their choice of a variety of forms and flavors of Rogue® nicotine products (Study Products) over a 6-month actual use period and completed online surveys assessing tobacco, nicotine and Study Product use at Baseline and Months 1, 2, 4, and 6 thereafter. Results Among the 1393 participants at Month 6, 41.4% and 52.5% used predominantly fruit/other or mint Study Product flavors, respectively. Compared to predominant mint users, predominant fruit/other users had greater cigarette reduction (mean reduction: 50.0% vs. 48.4%) and a higher proportion had quit smoking (proportion quit: 15.4% vs. 11.6%) at Month 6. Additionally, 38.8% of predominant fruit/other users and 39.3% of predominant mint users reduced their cigarette consumption by ≥ 50% from Baseline. Increased use of fruit/other flavors was independently associated with smoking reduction (8.6% greater reduction per 10 pieces/day; p < 0.001) and odds of quitting smoking (OR = 1.29 [95% CI: 1.04-1.59] per 10 pieces/day; p = 0.017). Increased use of mint flavors was independently associated with smoking reduction (7.5% greater reduction per 10 mint pieces/day; p < 0.001) but not with odds of quitting smoking. Conclusions Increased use of either fruit/other or mint flavored Study Products at Month 6 was associated with significantly increased smoking reduction, whereas only increased use of fruit/other flavors was associated with greater odds of quitting smoking among participants in the study. Trial Registration This study was observational. Participants were not prospectively assigned to one or more health-related interventions and could choose to use or not use the commercially available study products provided during the study. Thus, the study was not registered in a trial database by the Sponsor.